Morphology and multi-gene phylogeny reveal a new fungal genus and species from Hevea brasiliensis latex in Yunnan, China - Xu, Ruifang; Hyde, Kevin D.; Karunarathna, Samantha C.; Xu, Jian-Chu; Mortimer, Peter E.; Tibpromma, Saowaluck (Phytotaxa, 2022)
During a survey of rubber tree plantations in Yunnan Province, China, a fungus growing on natural rubber latex was collected and isolated. Maximum likelihood and Bayesian analyses of combined ITS, LSU, SSU, tef-α and rpb2 genes showed the isolated taxon belongs to Wiesneriomycetaceae and was well separated from closely related genera with high statistical support. It can be differentiated from other genera in Wiesneriomycetaceae by synnemata with catenate conidia that are cylindrical, 0–4 to multi-septate, often with a dark brown band at the septa. Morphology, phylogenetic analyses and pairwise homoplasy index (PHI) tests provide evidence that the new isolate is a distinct genus. The genus Heveicola is introduced, with H. xishuangbannaensis as the type species. A key to the genera in Wiesneriomycetaceae is also provided.